THE ROLE OF INTERNATIONAL EXPERIENCES IN THE DEVELOPMENT OF ENO(WINE) TOURISM IN TASHKENT REGION (The Conference Hub, 2025)
The article analyzes the concept of eno (wine) tourism, its global development paths and successful experience of leading countries. The possibilities of creating eno tourism based on the existing potential of viticulture, wine production enterprises and tourism infrastructure in the Tashkent region are studied. The ways and recommendations for adapting international experience to local conditions are presented.